PENERAPAN METODE DEMOSTRASI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SEKOLAH DASAR - Dahlina, Dahlina; Sabri, Tahmid; Kartono, Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to describe student learning outcomes in learning natural sciences using the demonstration method in class in the fifth grade public elementary school 08 Trans Magamagan Bengkayang. This study used descriptive qualitative method. Data collection techniques used are observation techniques and document scrutiny techniques with data collection tools namely observation sheets and document scoping sheets. The subjects in the study were students of class III Public Elementary School 08 Trans Magamagan Bengkayang totaling 12 people.The results of the study showed that the learning implementation plan (RPP) from cycle I was 3.17, cycle II was 3.32. The results of the study of the implementation of learning from the first cycle were 2.37, the second cycle was 3.56. The results of the learning outcomes of the first cycle average value of 63.33, cycle II an average value of 90. Based on the data obtained it can be concluded that there is an increase in each cycle. Thus research on the application of the class III learning method of learning Natural Sciences can improve student learning outcomes. Keywords: Learning Outcomes, Learning Natural Science, Demonstration Method